GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 396314 species occurrences available in GBIF matching the query: DatasetKey: British Lichen Society - BLS Lichen Database: English churchyards. The dataset includes 396314 records from 1 constituent datasets: 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences